Java project on periodontal diseases: causes of tooth loss in a cohort of untreated individuals - van der Velden, Ubele; Amaliya, Amaliya; Loos, Bruno G.; Timmerman, Mark F.; van der Weijden, Fridus A.; Winkel, Edwin G.; Abbas, Frank (Journal of clinical periodontology, 2015)
Objective To assess the relative contribution of caries and periodontal disease to tooth loss over 24 years in a cohort deprived of regular dental care. Material & Methods The study population consisted of 98 subjects from a tea estate on West Java, Indonesia, that had been part of a prospective longitudinal study and provided full datasets of clinical assessments between 1987, 1994 and 2002. In 2011, complete sets of dental radiographs were made which was combined with the survey forms and clinical slides from the previous assessments in order to estimate reasons for tooth loss. Results Thirty‐seven subjects lost no teeth, whereas 61 subjects lost 185 teeth. In this group, 45.9% lost ≤2 teeth, 32.8% lost 3 to 4 teeth and 19.7% lost ≥5 teeth. The majority of teeth were lost due to caries. In five subjects, tooth loss could be attributed solely to periodontitis, whereas in four subjects teeth were lost due to both caries and periodontits. Analyses of the predictor variables age, gender, smoking, education, presence of caries and severe periodontitis showed that male gender and caries were significantly associated with tooth loss. Conclusion The majority of teeth in this population were lost due to caries.